FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS DOKUMENTASI ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT ISLAM IBNU SINA PADANG - Clara Nadia; Hafni Bachtiar; Reni Prima Gusty (Ensiklopedia of Journal, 2023)
Quality nursing care can be imaged on the documentation of the nursing process. Besides completeness important also assess the quality of nursing care documentation that has been done by nurses. The results of the evaluation of 2015 is 68.6% still do not reach the standards of the Department of Health (2005) is 75%. This study aims to determine the factors associated with the quality of nursing care documentation. This type of research is analytic with cross sectional study. Number of samples 45 nurses in patient wards with proportional random sampling technique sampling. Bivariate data analysis with chi-square and multivariate logistic regression. The results showed nurses young adulthood (84.4%), nurses with relatively long duration of action (55.6%), good motivation (53.3%), supervision of nursing care documentation is good (55.6%), good rewards (57.8%), and the quality of nursing care documentation was not good (53.3%). There was not relationship between age and length of employment with the quality of nursing care documentation. There was relationship between motivation, supervision and rewards the quality of nursing care documentation. Supervision is a dominant factor in the quality of nursing care documentation. Suggested to hospital managers to evaluate the documentation format with checklist method, technique instructions to socialize and make related policy of reward and punishment in the implementation of nursing care documentation.